2010
DOI: 10.2136/vzj2009.0149
|View full text |Cite
|
Sign up to set email alerts
|

Artificially Drained Catchments—From Monitoring Studies towards Management Approaches

Abstract: Artificial drainage is successfully used to improve the moisture conditions of agricultural soils, but there are drawbacks, such as nutrient export and wetland destruction. This Special Section: Artificial Drainage of the Vadose Zone Journal features eight papers comprising diverse subjects, including the history of land drainage in England, monitoring strategies, nutrient losses under different management systems, and constructed wetlands to mitigate pollution from tile drainage. Still, there are issues such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…The implemented exchange model followed the Gapon convention [51] with Ca 2+ as the reference cation. The sediment cation exchange capacity was calibrated, yielding a value (11.9 cmol/kg) in line with that measured by Baker et al [50] (21 cmol/kg) and other data cited by these authors (0.9-45 cmol/kg) for INL site materials.…”
Section: Methodssupporting
confidence: 66%
See 1 more Smart Citation
“…The implemented exchange model followed the Gapon convention [51] with Ca 2+ as the reference cation. The sediment cation exchange capacity was calibrated, yielding a value (11.9 cmol/kg) in line with that measured by Baker et al [50] (21 cmol/kg) and other data cited by these authors (0.9-45 cmol/kg) for INL site materials.…”
Section: Methodssupporting
confidence: 66%
“…Ion selectivity coefficients for INL sediments from Baker et al [50] were used, except for K + , for which no data were reported by these authors, and for which the same selectivity as for Na + was assumed. The implemented exchange model followed the Gapon convention [51] with Ca 2+ as the reference cation.…”
Section: Methodsmentioning
confidence: 99%
“…Man‐made features changes in small rural catchments may concern the planning of tillage practices (Mwendera and Feyen, 1994; Yu et al , 2000), tile drainage (Tiemeyer et al , 2007; Lennartz et al , 2010), ditch networks (Carluer and De Marsily, 2004), water‐harvesting systems (Ouessar et al , 2009) or riparian areas (McKergow et al , 2003). Some land management scenarios on small catchments may be compared using distributed modelling.…”
Section: Introductionmentioning
confidence: 99%
“…The precipitation surplus is often discharged via dense, partially man-made drainage systems (Lennartz et al, 2009). For individual fields, drainage theory based on analytical solutions for the predominantly horizontal flow in the phreatic aquifer has proven its value for several decades (Hooghoudt, 1940;Dumm, 1954;Kraijenhoff van de Leur, 1958;van Schilfgaarde, 1970).…”
Section: Introductionmentioning
confidence: 99%